The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/ps.3831
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship studies of the phytotoxic properties of the diterpenic moiety of breviones

Abstract: The results clearly show that expanded phenanthrene-like compounds corresponding to the diterpenic moiety of abeo-brevianes are more selective towards E. crus-galli in comparison with L. rigidum. Such selectivity can reach up to one order of magnitude (200-fold) and makes some of the compounds good candidates as leads for the development of more specific herbicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several studies suggested that CHFR gene expression is frequently silenced by promoter hypermethylation in gastric cancer 8-12. Additionally, CHFR promoter methylation improved the gastric cancer sensitivity to microtubule inhibitors such as docetaxel and paclitaxel 13, 14. However, the samples of these studies were too small to confirm solid results.…”
Section: Introductionmentioning
confidence: 88%
“…Several studies suggested that CHFR gene expression is frequently silenced by promoter hypermethylation in gastric cancer 8-12. Additionally, CHFR promoter methylation improved the gastric cancer sensitivity to microtubule inhibitors such as docetaxel and paclitaxel 13, 14. However, the samples of these studies were too small to confirm solid results.…”
Section: Introductionmentioning
confidence: 88%
“…Diterpenes and sesquiterpene lactones are two large families of widely studied natural products that show a broad range of biological activities. For example, diterpenes are known as anticancer, anti-diabetic (Nagarajan and Brindha, 2012), anti-inflammatory (Kapewangolo et al, 2015), anti-oxidant (Kolak et al, 2009) or phytotoxic compounds (Carrera et al, 2015). In contrast, sesquiterpene lactones have been reported to show a variety of activities, such as antimicrobial, antitumour, anti-inflammatory, cytotoxic, antiviral, antimalarial, antibacterial and antifungal.…”
Section: Introductionmentioning
confidence: 99%
“…Polyketides, a series of metabolites derived from polyketide synthases (PKS), always show abundant structure diversities and also various pharmaceutical potentials . However, there are only a few herbicidal assessments of natural polyketides and no herbicidal reports of the heptaketide series bearing the trans -fused decalin skeleton. Therefore, the isolation and significant herbicidal potentials of new polyketides 1 – 3 and known 4 could not only enrich the structure diversities of herbicide metabolites from microbes but also exhibit a herbicide heptaketide skeleton, which might also show the potential of new target sites.…”
Section: Resultsmentioning
confidence: 99%